Topology Optimization Analysis and Development of a Bracket Using Simulation and Additive Manufacturing (AM) Technology - Noorazli, Nur Aina (IRC, 2018)

(untitled)
Conventional methods are not simple or are close to impossible to be used to fabricate topology optimized structures as the final design of topology optimized parts are too complex. The benefit of topology optimized parts and Additive Manufacturing Technology integrate to form an opportunity to fabricate light- weight topology optimized parts. Weight reduction structures based on a clamp design is analysed with regards to the tensile/compressive yield strength, weight reduction percentage, total deformation and maximum stress experienced. The constraints that limit the designs are the yield strength and the weight reduction percentage. The parameters which are the changing variables that are dependent on the weight reduction are used to determine whether a structure is at the point of failure or not. The maximum stress and total deformation experienced evaluate the condition and performance of the structure. With this, a selection of the most optimal optimized structure can be done. The aim is to select the most weight reduced structure experiencing the least stresses. The selected structure will then be fabricated using Additive Manufacturing and later investment casted. ANSYS Static Structural and Topology Optimization modules were used to develop the model design, topology optimized, refining optimized structures and conduct simulations on the optimized structures. The simulation results and graph of constraints and parameters that is plotted shows that the 40% weight reduction structured is the most optimized.